Composto orgânico no estado nutricional de tangerineira 'Poncã' - Ramos, Dayana Portes (2014)
The work was conducted in Experimental Farm of the Faculdade de Ciências Agronômicas/ UNESP. The treatments consisted of doses of 50, 100, 150 and 200% of nitrogen present in organic compost, plus the control treatment, equaling an average of 3 years of applications: T1 = 0 g plant-1 N (Witness), T2 = 128 g plant-1 of N, T3 = 256.0 g plant-1 of N, T4 = 384 g plant-1 of N and T5 = 512 g plant-1 of N. The experimental design was completely randomized with five treatments (doses) with four replications in a split plot, with the fertilizer applied to main plots and times of assessments applied to the subplots. Each plot consists of two plants. The effects of organic manure were evaluated by chemical analysis of macro and micronutrients in the leaves, before fertilization and after six months this for two production cycles, corresponding to the 2009, 2010 and 2011 years. The average data concerning the four samples were subjected to analysis of variance and regression in each evaluation. Also, it was evaluated the yield. Leaf analyzes showed that the nitrogen levels in leaves were considered adequate, after three years with fertilization with organic compost. The yield increase with the increase of the levels of organic compost in the first year and in the second year, there was not significant differences between the levels of organic compost.